ANALYSIS COMPARISON OF THE 7PâS ELEMMENTS OR CONSUMER PURCHASING DECISION BETWEEN AQUA AND AKE MINERAL WATER IN MANADO - Rompis, Reyti Riansye (Sam Ratulangi University, 2015)
ABSTRACT The speedy changing on the economic aspect, especially at the marketing concept, the products or services recognition to used by the majority of businessmen for creating each good or service that can be really accepted by almost all customers in the marketplace. The study aims to determine the significant difference for the concept of: 1) product; 2) price; 3) place; 4) promotion; 5) people; 6) physical evidence concept; 7) process; 8) 7Ps and 9) Consumer Purchasing Decision between Aqua and Ake mineral water products purchasing in Manado. The result show 1) There is any significant difference for product, price, place, people, and 7Ps Customer Purchase Decision Concept between Aqua and Ake mineral water products purchasing in Manado; and 2) There is no significant difference for promotion and physical evidence factor between Aqua and Ake mineral water products purchasing in Manado. Keywords: 4Ps, 7Ps, Product, Price, Place (Distribution), Promotion, People, Physical Evidence, Process, Customer Purchase Decision